PENGARUH THEOSOFI DAN FREEMASON DI INDONESIA (Kajian Analitis Simbol-simbol Theosofi dan Freemason dalam Lirik Lagu dan Sampul Kaset Album Grup Musik Dewa 19) - Prihatno, Setyahadi (Profetika, 2016)
The lyrics and album cover of Dewa 19 wave of criticism with many symbols or emblemsthat allegedly represent the ancient mystical beliefs and visually turns almost identicalto the symbols on the Thesofi anf Freemason. It lead to the possibility of meaning similarity.Four main points discussed in this study is about the meaning of the lyrics of the albumâssongs of Dewa 19 band, regarding the visual appearance and meaning of symbols in the coverof the album of Dewa 19, reviewing the structure of the relationship between the lyrics and thesymbols in the album of Dewa 19 with Theosofi and Freemason, as well as explain the impactof visualization and dissemination of these symbols in a album of Dewa 19 cassette. Dewa 19has consistently display the lyrics of songs and symbols of Theosofi and Freemasonry teachingsstarted from his first album. Symbols are cleverly laid out in various ways and can onlybe seen with certain ways. The pattern of symbols has a characteristic appearance as well asits own theme. The structure of relations that are drawn in this study relates to the profile ofAhmad Dhani, Theosofi and Freemason teachings, text and lyrics, as well as a visual displayof Theosofi and Freemasons symbols in Dewa 19 album. Display representations of symbolscontained in the album cover of Dewa 19 concluded have relevance in form and meaning tothe symbols of the teachings or understood Occult, Paganism, Kaballah and Theosofi, as wellas movements such as secret Zionist, Illuminati and Freemasonry.Keywords: symbol; theosofi; freemason.Abstrak: Lirik dan sampul album Dewa 19 menuai banyak kritik dengan banyaknya simbolatau lambang yang diduga merepresentasikan kepercayaan mistik kuno dan secara visualternyata nyaris identik dengan simbol-simbol pada Theosofi dan Freemason.Hal tersebutmengarahkan pada adanya kemungkinan kesamaan makna. Empat hal utama yang dibahasdalam penelitian ini adalah mengenai makna dari lirik lagu album grup musik Dewa 19, mengenaitampilan visual dan makna simbol dalam sampul album Dewa 19, mengkaji strukturrelasi antara lirik lagu dan simbol dalam album Dewa 19 dengan Theosofi dan Freemason,serta menjelaskan dampak dari visualisasi dan penyebaran simbol-simbol tersebut dalam kasetalbum Dewa 19. Dewa 19 secara konsisten telah menampilkan lirik lagu dan simbol-simbolajaran Theosofi dan Freemason dari mulai album pertamanya. Simbol secara cerdik diletakkandengan berbagai cara dan hanya bisa dilihat dengan cara-cara tertentu. Pola pemunculan simbolmemiliki ciri serta tema tersendiri. Struktur relasi yang ditarik dalam penelitian ini berkaitandengan profil Ahmad Dhani, ajaran Theosofi dan Freemason, teks dan lirik lagu, sertatampilan visual simbol-simbol Theosofi dan Freemason dalam album Dewa 19. Representasitampilan simbol yang terdapat dalam sampul album Dewa 19 disimpulkan memiliki keterkaitansecara bentuk dan makna dengan simbol-simbol dari ajaran atau paham Okultisme,Paganisme, Kaballah serta Theosofi, serta pergerakan-pergerakan rahasia Zionisme Yahudi seperti, Illuminati dan Freemasonry.Kata kunci: symbol; theosofi; freemason.